STATUS OF PERSON WITH DISABILITIES AND THE SOCIAL MODEL OF DISABILITIES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article deals with the alteration caused by the Statute of the Person with Disabilities in the way of perceiving the disability by society and by law, through the social model. Based on the principles of human dignity, equality and accessibility, this with a broader bias than the elimination of mobility barriers, the social disability model establishes the society's duty to provide the means, services and instruments for people with disabilities are included to the greatest extent possible. Therefore, it is everyone's duty to eliminate all barriers that prevent or hinder the exercise of rights by people with disabilities, such as technological, service and mobility barriers.